2019
DOI: 10.1214/19-aoas1249
|View full text |Cite
|
Sign up to set email alerts
|

RCRnorm: An integrated system of random-coefficient hierarchical regression models for normalizing NanoString nCounter data

Abstract: Formalin-fixed paraffin-embedded (FFPE) samples have great potential for biomarker discovery, retrospective studies and diagnosis or prognosis of diseases. Their application, however, is hindered by the unsatisfactory performance of traditional gene expression profiling techniques on damaged RNAs. NanoString nCounter platform is well suited for profiling of FFPE samples and measures gene expression with high sensitivity which may greatly facilitate realization of scientific and clinical values of FFPE samples.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…We benchmarked RUVSeq and nSolver with two other normalization methods, NanoStringDiff [13] and 2 RCRnorm [14]. We observed differences across the four normalization strategies (described in 2 Supplemental Table S2), namely greater remaining technical variation using nSolver and NanoStringDiff 2 than RCRnorm and RUVSeq (Figure 2B-D).…”
Section: Evaluation Of Normalization Methodsmentioning
confidence: 99%
“…We benchmarked RUVSeq and nSolver with two other normalization methods, NanoStringDiff [13] and 2 RCRnorm [14]. We observed differences across the four normalization strategies (described in 2 Supplemental Table S2), namely greater remaining technical variation using nSolver and NanoStringDiff 2 than RCRnorm and RUVSeq (Figure 2B-D).…”
Section: Evaluation Of Normalization Methodsmentioning
confidence: 99%
“…However, information provided by different types of probes is intermingled. Instead of correcting the different biases in an isolated manner, which is typical in existing methods, Jia et al 4 proposed an integrated system of random‐coefficient regression models for jointly modeling log‐transformed read counts from the different types of probes. For the i th sample (i=1,,I), let Yip+, Yin, Yih, and Yir denote the log10 transformed read count of the p th positive control (p=1,,P), the n th negative control (n=1,,N), the h th housekeeping gene (h=1,,H), and the r th regular gene (r=1,,R), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Using information from the different types of internal controls, several analysis methods have been developed for the nCounter platform to normalize and extract gene expression levels, such as NanoStringNorm, 1 NAPPA, 2 and NanoStringDiff 3 . Recently, Jia et al 4 proposed a novel Bayesian method called RCRnorm, which consists of a system of random‐coefficient hierarchical regression (RCR) models, attempting to accurately characterize different types of probes. It has been shown that RCRnorm compares favorably with other existing methods, especially for situations with an elevated level of heterogeneity from various sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CBCS data, we compared the normalized datasets from nSolver, RUVSeq, NanoStringDiff [13], 1 and RCRnorm [14] with the raw data through visualization methods outlined above (Figure 1 Table S2. 1 1 that RUVSeq best addressed the largest source of technical variation identified in the raw data ( Figure 3 2D; Supplemental Figure S5A) while also not removing a significant portion of biological variation 3 (Supplemental Figure S5B).…”
Section: Alternative Normalization Methods For Benchmarkingmentioning
confidence: 99%